Investigation of the effects of silica coating on the thermal conductivity and porosity of aluminum nitride after sintering. Issue 4 (2nd October 2019) - Kita, Ken'Ichiro; Kondo, Naoki
ABSTRACT: This paper describes a method of applying a silica coating on aluminum nitride and investigations concerning the thermal conductivity between the coating layer and the aluminum nitride as well as the effect of the silica coating layer on the density of samples containing aluminum nitride and glass after sintering. The coating was carried out using polycarbosilane that was transformed into silica by pyrolysis under an airflow. The measured thermal conductivities of all the samples were within an error of less than 10 W/m·K. The porosity of a sintered sample containing the silica-coated aluminum nitride powder and glass powder was decreased by about 10% compared to that of a sintered sample comprising pure aluminum nitride powder.